INFLUENCE OF THICKNESS ON THE PROPERTIES OF TiO2 AND Ti(Nb)O2 THIN FILMS - SUCHEA, Mirela; VAMVAKAKI, Maria; LOULOUDAKIS, Dimitris; SIGALAS, Michael; KATSARAKIS, Nikolaos; VERNARDOU, Dimitra; KOUDOUMAS, Emmanuel (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Pure and Nb doped titanium dioxide films were grown by magnetron sputtering, for integration in hybrid polymer-semiconductor solar cells. The effect of the thickness of the films on their physical properties was investigated, emphasis given on the optical transparency, the surface morphology, the wettability and the conductivity. Particular surface parameters were determined and their variation with film thickness was investigated. Finally, a hydrophobic to hydrophilic transition under UV irradiation was studied.